Hydrolytic and Oxidative Stability of l -(+)-Ascorbic Acid Supported in Pectin Films: Influence of the Macromolecular Structure and Calcium Presence - Pérez, Carolina Daiana (2012)
The hydrolytic and oxidative stability of L-(+)-ascorbic acid (AA) into plasticized pectin films were separately studied in view of preserving vitamin C activity and/or to achieve localized antioxidant activity at pharmaceutical and food interfaces. Films were made with each one of the enzymatically tailored pectins (50%, 70%, and 80% DM; Cameron et al. Carbohydr. Polym. 2008, 71, 287−299) or commercial high methoxyl pectin (HMP; 72% DM). Since AA stability was dependent on water availability in the network, pectin nanostructure affected the AA kinetics. Higher AA retention and lower browning rates were achieved in HMP films, and calcium presence in them stabilized AA because of higher water immobilization. Air storage did not change AA decay and browning rates in HMP films, but they significantly increased in Ca-HMP films. It was concluded that the ability of the polymeric network to immobilize water seems to be the main factor to consider in order to succeed in retaining AA into film materials.